Rhizomucor mieheiLipase nanoconjugates for visualizing latent fingermarks on wet glass slides: bioinformatics, characterization and laboratory assessment - Nik Razi, Nik Ihtisyam Majdah; Mahat, Naji Arafat; Azman, Aida Rasyidah; Abdul Wahab, Roswanira; Oyewusi, Habeebat Adekilekun; Abdul Hamid, Azzmer Azzar; Nordin, Norita (UTM Press, 2026)
Developing latent fingermarks on wet, non-porous substrates presents significant challenges, and conventional Small Particle Reagent (SPR) method often involvestoxic components. Existing nanobio-based reagents for fingermark development exhibit a limited fatty acid spectrum. Consequently, investigating the broader ligand specificity of Rhizomucor mieheilipase (RML) nanoconjugate(nanobio-based reagent1, NBR-1) as a potential fingermark biosensor is pertinent.Molecular docking analysis determined the binding affinities of NBR-1 for decanoic, palmitic, docosanoic, and stearic acids to be -4.9, -5.5, -6.1, and -6.8 kcal/mol, respectively. Molecular dynamics simulations, assessed viaroot mean square deviation (RMSD), root mean square fluctuation (RMSF), radius of gyration (Rg), hydrogen bond count, and Molecular Mechanics Poisson-Boltzmann Surface Area (MM-PBSA) analysis, confirmed stable complex formation in all cases, evidenced by consistent hydrogen bonding (distances: 2.2–3.4 Å). NBR-1 characterization by Attenuated Total Reflectance-Fourier Transform Infrared spectroscopy revealed that RML immobilization on F-MWCNTs (NBR-1) was evidenced by a shift of the amide C=O stretch from 1640 to 1653 cm⁻¹ and by the reduced intensity and broadening of the carboxylate C–O peak at 1256 cm⁻¹, confirming polypeptide chain presence.Field Emission Scanning Electron Microscopy demonstrated the increment in the RML thickness, providing evidence for successful RML molecule attachment to the F-MWCNT surface. Under controlled laboratory conditions, the synthesized NBR-1 reagent successfully developed latent fingermarks (exhibiting low background noise) on glass slides submerged in water for periods of 7 and 14 days. These empirical findings corroborate the initial bioinformatic predictions.Therefore, the results robustly validate NBR-1 as a promising candidate technology for visualizing latent fingermarks, specifically on water-immersed, wet non-porous surfaces, in forensic contexts.